1978
DOI: 10.1113/jphysiol.1978.sp012130
|View full text |Cite
|
Sign up to set email alerts
|

Glucose transport by brush‐border membrane vesicles after proximal resection or ileo‐jejunal transposition in the rat.

Abstract: SUMMARY1. The functional properties of the ileal mucosa following jejunal resection or interposition in the jejunum were studied with the help of membrane vesicles.2. Despite the development of functional and morphological features in the mucosa which are more generally associated with the jejunum than with the ileum, examination of brush-border vesicles derived from ileal and jejunal enterocytes from resected or transposed intestines reveals that the functional characteristics of apical membranes isolated fro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
14
0

Year Published

1978
1978
2015
2015

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(15 citation statements)
references
References 14 publications
1
14
0
Order By: Relevance
“…Glucose transport into isolated brush border membrane vesicles is unaltered by intestinal resection (Menge, Murer & Robinson, 1978). Recent studies (Urban & Michel, 1983) have demonstrated that morphological growth preceded and did not parallel functional adaptation.…”
Section: Introductionmentioning
confidence: 99%
“…Glucose transport into isolated brush border membrane vesicles is unaltered by intestinal resection (Menge, Murer & Robinson, 1978). Recent studies (Urban & Michel, 1983) have demonstrated that morphological growth preceded and did not parallel functional adaptation.…”
Section: Introductionmentioning
confidence: 99%
“…67], but the life span of the cells may be unchanged [68] or shortened [69], If this decreased life span can be inter preted in terms of a diminished maturation of the enterocytes, the results [70] of a de creased microvillus surface area in the villus compartment may be the morphological re flection of an immature cell state. Quantita tive histochemical data [71] point in the same direction: after proximal resection, en zyme activities of two disaccharidases did not change at the base of the villi, whereas in the case of a-glucosidase the Vmax values were reduced at the transition zone between the middle and apical third of the villi in the hypoplastic mucosa, while other enzyme ac tivities remain unchanged. In spite of the unchanged absorptive capacity of the indi vidual enterocytes in the hyperplastic mu cosa which has been demonstrated by auto radiographic studies, [26], and by the inves tigations on BBM vesicles.…”
Section: Patterns and Mechanisms Of Adaptation Of Intestinal Transportmentioning
confidence: 76%
“…Menge et al [10] found no increase in glucose uptake into brush border membrane vesicles 1 month after surgery and Weser and Hernandes [12], who measured glucose uptake into isolated cells, also did not find an increase under the conditions of the short bowel syndrome 5-6 weeks after sur gery. Two reasons may be responsible for this discrepancy to our present findings.…”
Section: Discussionmentioning
confidence: 99%